2017
DOI: 10.1039/c7ra08761f
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of acid corrosion on carbon steel by novel pyrazolone derivatives

Abstract: For the corrosion of carbon steel in 1.0 M HCl solution, the new pyrazolone derivatives (PY1 and PY2) have been identified as active corrosion inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Some pyrazolones have been used as fungicides and herbicides for crop protection, as dyes for cotton, wool, and silk, 3 as ligands for synthesis of metal complexes, 8 and as corrosion inhibitors. 9 Pyrazolones can exist in three tautomeric forms ( Fig. 1A) known as 3-pyrazolone (CH form), 4-pyrazolone (OH form), and 5-pyrazolone (NH form).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pyrazolones have been used as fungicides and herbicides for crop protection, as dyes for cotton, wool, and silk, 3 as ligands for synthesis of metal complexes, 8 and as corrosion inhibitors. 9 Pyrazolones can exist in three tautomeric forms ( Fig. 1A) known as 3-pyrazolone (CH form), 4-pyrazolone (OH form), and 5-pyrazolone (NH form).…”
Section: Introductionmentioning
confidence: 99%
“…Some pyrazolones have been used as fungicides and herbicides for crop protection, as dyes for cotton, wool, and silk, 3 as ligands for synthesis of metal complexes, 8 and as corrosion inhibitors. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In the presence of BPTU, the OCP tends to shift towards negative potentials. e drop of OCP during the first 3000 seconds may be due to the dissolution of the oxide layer that formed previously when the low carbon steel contacted with the atmosphere [37]. erefore, the immersion time of one hour is chosen to reach a certain state for potentiodynamic polarization measurements.…”
Section: Open Circuit Potential (Ocp)mentioning
confidence: 99%
“…To control corrosion of the metal, its surface needs to be masked significantly with an organic or an inorganic interdict material to be segregated from corrosive territory or domain [8][9][10]. Application of molecules as an interdict species is the finest and most reliable practical technique to shield the metal from dissipation in an acidic medium [11][12][13]. It was reported that 4aminoacetophenonepyridine 2-aldehyde (4AAPA) inhibits the corrosion of the mild steel in 1 N HCl and maximum inhibition of 91% was achieved at a concentration of 60 ppm [14].…”
Section: Introductionmentioning
confidence: 99%